Providing ultra‐short latency to user‐centric 5G applications at the mobile network edge - Farris, I.; Taleb, T.; Flinck, H.; Iera, A. (Transactions on emerging telecommunications technologies, 2018)
Mobile Edge Computing (MEC) will play a key role in next‐generation mobile networks to extend the range of supported delay‐sensitive applications. Furthermore, an increasing attention is paid to provide user‐centric services, to better address the strict requirements of novel immersive applications. In this scenario, MEC solutions need to efficiently cope with user mobility, which requires fast relocation of service instances to guarantee the desired Quality of Experience. However, service migration is still an open issue, especially for resource‐constrained edge nodes interconnected by high‐latency and low‐bandwidth links. In this paper, by leveraging the potential of lightweight container‐based virtualization techniques, we investigate a novel approach to support service provisioning in dynamic MEC environments. In particular, we present a framework where proactive service replication for stateless applications is exploited to drastically reduce the time of service migration between different cloudlets and to meet the latency requirements. The performance evaluation shows promising results of our approach with respect to classic reactive service migration. MEC solutions need to efficiently cope with user mobility, which requires fast relocation of service instances to guarantee the desired latency requirements. In this paper, by leveraging the potential of lightweight container virtualization, we investigate a proactive service replication approach for stateless applications, to drastically reduce the time of service migration between different edge nodes. The performance evaluation shows promising results of our approach with respect to classic reactive service migration.